PENGENALAN AKUNTANSI PERUSAHAAN DAGANG PADA SISWA-SISWI SMA TARSISIUS 1 JAKARTA - Sylvia; Syanti Dewi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
The knowledge of financial recording is essential and needs to be mastered by every individual. High school students need to learn the basics of accounting to help them manage finances (budgeting) and making economic decisions from an early age. Knowing this urgency, unfortunately, basic accounting topics in the high school curriculum, including Tarsisius 1 High School, are not discussed comprehensively because there is a lot of other material that also needs to be discussed. Based on these problems, the Tarumanagara University PKM group held an Accounting Introduction for Trading Company activity at Tarsisius 1 High School Jakarta as a forum for students to deepen their knowledge of accounting and help prepare them to take the next level of education. This activity was carried out on Wednesday for 90 minutes and was divided into 3 (three) stages, such as theoretical explanation, discussion of example questions, and implementation of a quiz with prizes. Based on the quiz results, it can be concluded that the participant's understanding of the material presented has increased. Participants can apply the theory presented in answering questions that have been prepared according to real-world case examples. This PKM activity has proven capable of providing additional accounting knowledge for Tarsisius 1 High School students outside of school learning and has increased interest in accounting. Based on the matters described previously, it can be concluded that the PKM activities at Tarsisius 1 High School had been successful and were able to provide benefits in accordance with the objectives.